Globalization, Development and the Mass Media - Colin Sparks (Sage, 2007)
This book gives a comprehensive and critical account of the theoretical changes in communication studies from the early theories of development communication through to the contemporary critiques of globalization. It looks at the ways in which the media can be used to effect change and development, and traces the evolution of thinking from attempts to spread ′modernity′ by way of using the media through to alternative perspectives based on encouraging participation in development communication. It explores the theory of media imperialism, the criticisms that it provoked, and its replacement as the dominant theory of international communication by globalization.